Pengaruh Persepsi Kemudahan Terhadap Minat Mahasiswa Dalam Menggunakan Financial Technology P2P Lending Pada Masa Pandemi (Studi Kasus Pada Mahasiswa Kota Bandung) - Nadiati Arifha Nurani; Riauli Susilawati (Indonesian Accounting Research Journal, 2023)
The purpose of this study was to analyze the effect of perceived convenience on student interest in using online credit financial technology. Covid-19 Pandemic has brought many changes in Indonesia, one of the example that can be felt is a fact that this pancemic is making the economy in Indonesia significantly decline, often makes people do various ways to earn income to support their daily needs. Online loan financial technology creates an online platform that provides people with direct loans that helps many people. It become easier for them to make online lending transactions. This study uses the Technology Acceptance Model in examining how easy perceptions affect student interest in using online loan financial technology which explains that the magnitude of the coefficient of determination is 5.3% of the User Interest variable which is influenced by Perception of Ease, while the opposite is influenced by other things.